1995
DOI: 10.1080/15287399509531973
|View full text |Cite
|
Sign up to set email alerts
|

Histone nuclear proteins are irreversibly modified by reactive metabolites of diethylstilbestrol

Abstract: We demonstrate for the first time that diethylstilbestrol (DES), a synthetic estrogen, is converted by nuclei to histone-binding metabolite(s). Reaction of [3H]DES with nuclei in the presence of cumene hydroperoxide or NADPH revealed binding of [3H]DES to histone nuclear proteins. Gel electrophoresis experiments revealed that all five histones, 1, 2A, 2B, 3, and 4, were irreversibly bound to [3H]DES. Histones 1 and 3 were more susceptible to the attack by [3H]DES quinone, a metabolite of DES, than histones 2A,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…DES exposure during pregnancy has been shown to alter the miRNA expression of oncogenic miRNAs in both fetus and mother [127] . Similarly, studies have also shown that DES affects histone modifications [128] . Warita et al [129] showed that the P450scc promoter region is deacetylated upon treatment with DES.…”
Section: Exposure To Diethylstilbestrolmentioning
confidence: 99%
“…DES exposure during pregnancy has been shown to alter the miRNA expression of oncogenic miRNAs in both fetus and mother [127] . Similarly, studies have also shown that DES affects histone modifications [128] . Warita et al [129] showed that the P450scc promoter region is deacetylated upon treatment with DES.…”
Section: Exposure To Diethylstilbestrolmentioning
confidence: 99%